检测Ⅰ期肺癌患者血清C反应蛋白的预后意义 (Zhongguo Fei Ai Za Zhi, 2011)
BACKGROUND AND OBJECTIVE: The acute inflammatory, as manifest by alterations in white cell count and circulating concentrations of acute-phase proteins, C-reactive protein (CRP), and albumin, has been shown to be an independent prognostic factor in various cancers including non-small cell lung cancer (NSCLC). The aim of this study is to observe the relation between CRP level before operation and clinical characteristics of NSCLC stage Ⅰ, and its prognostic value. METHODS: Data of ninety-six NSCLC stage Ⅰ cases under total operational excision from Jan 2000 to Jan 2004 were reviewed. The difference of CRP level in different characteristics was analyzed by ANOVA. Distributions and comparisons of survival according to CRP level were analyzed by Kaplan-Meier and Log-rank test. COX regression model was used to analyze prognostic factors of NSCLC. RESULTS: Sixty-six cases had a CRP level of ≤5 mg/L. The level of CRP in patient with squamous cell carcinoma was remarkably higher than that with nonsquamous cell carcinoma (P < 0.001). The CRP level in tumor diameter > 3 cm was significantly higher than that in tumor diameter < 3 cm (P < 0.001). Multiple linear regression analysis suggested the maximum diameter of tumor was closely related to the level of serum CRP. The 5-year survival rate was lower in CRP > 5 mg/L group than that in CRP≤5 mg/L group (54.1% vs 78.2%, P=0.021). COX model found CRP level was an independent prognostic factor of stage Ⅰ NSCLC. CONCLUSION: The pre-operational CRP level of stage Ⅰ NSCLC is positively related to the maximum diameter of tumor. CRP level is probably a poor prognostic factor for stage Ⅰ NSCLC.